Relationship Between Students’ Learning Outcomes in WAEC and NECO Arabic Language Examinations in North-Central Nigeria - Musa Siddiq Abdullahi; Abdul Ganiy Abdus Salaam Oladosu (International Journal of Islamic Educational Psychology, 2021)
Despite the fact that the certificates being awarded by senior school WAEC and NECO are said to be comparable, yet, stakeholders in the education sector doubt their correspondence in terms of students’ learning outcomes. While some students only register for NECO believing that they could not pass WAEC. This was part of what necessitated this study by determining the correspondence between students’ learning outcomes in senior school WAEC and NECO Arabic Language examinations in North-central from 2015 to 2019 academic sessions. This study was a descriptive study of the correlational type. Only the results of candidates that sat for WAEC and NECO Arabic Language examinations were logically selected for this study via a researcher-designed proforma. Thus, 948 students constituted the sample size for this study using a multistage sampling procedure. Data collected were analyzed using the percentage to answer the research questions while the Pearson’s chi-square at 0.05 alpha level was used to test the hypotheses. Findings indicated that a significant association existed between students’ learning outcomes in WAEC and NECO Arabic examinations in North-central Nigeria. It was therefore recommended that teachers of Arabic should work harder to sustain their students’ performance in Arabic Language.